Effects of extremely high temperatures on some growth parameters of sessile oak (Quercus petraea /Matt./Liebl.) seedlings in northeastern Serbia - Krstić, Milun R.; Kanjevac, Branko R.; Babić, Violeta P. (Archives of Biological Sciences, 2018)
Paper description: Extreme climate events such as heat and cold waves, ice storms etc. occur with increasing frequency, are the result of climate change which has a significant influence on tree species, especially during young phase of their development. Resistance of sessile oak seedlings to extremely high temperatures increases with age, while the stand canopy has a crucial role in the protection of young sessile oak seedlings from the dangers of high temperatures. The obtained results are important for planning measures related to sessile oak regeneration and development. Abstract: This paper presents research results on the effects of the extremely high temperatures during the heat wave of August 2017 on the growth and development of injury symptoms in sessile oak (Quercus petraea /Matt./Liebl.) seedlings of different age in the area of the Majdanpek municipality in northeastern Serbia. The starting hypotheses of this study is that the resistance of sessile oak seedlings to extremely high temperatures changes with age and that the stand canopy has a significant protective role in situations where sessile oak seedlings are endangered by extremely high temperatures. The extreme weather conditions at the beginning of August manifested themselves in extremely high temperatures and prolonged absence of precipitation. The average temperature at the beginning of August 2017 was 5.0 to 5.1ºС (depending on the altitude) higher compared to the period of seedling growth (2010-2016). During the heat wave, the recorded precipitation was in the range from 0 to 1 mm. These climate conditions significantly affected the development of young seedlings, causing wilting of smaller or larger parts of the leaf surface and sometimes leading to plant death. Using analysis of variance, differences in the intensity of seedling damage were found to depend on age, height, and the protection provided by the mature stand canopy. The obtained results point to the very important role of mature trees in the protection of seedlings from the dangers of extremely high temperatures. https://doi.org/10.2298/ABS171215013K Received: December 15, 2017; Revised: March 2, 2018; Accepted: March 26, 2018; Published online: March 30, 2018 How to cite this article: Krstić MR, Kanjevac BR, Babić VP. Effects of extremely high temperatures on some growth parameters of sessile oak (Quercus petraea/Matt./Liebl.) seedlings in northeastern Serbia. Arch Biol Sci. 2018;70(3):…